Strategies to Maintain Natural Biocontrol of Soil-Borne Crop Diseases During Severe Drought and Rainfall Events - Meisner, Annelein; de Boer, Wietse (Frontiers in Microbiology, 2018)
In many parts of the world, agricultural ecosystems are increasingly exposed to severe drought and rainfall events due to climate changes. This coincides with a higher vulnerability of crops to soil-borne diseases, which is mostly ascribed to decreased resistance to pathogen attacks. However, loss of the natural capacity of soil microbes to suppress soil-borne plant pathogens may also contribute to increased disease outbreaks. In this perspectives paper, we will discuss the effect of extreme weather events on pathogen-antagonist interactions during drought and rainfall events and upon recovery. We will focus on diseases caused by root-infecting fungi and oomycetes. In addition, we will explore factors that affect restoration of the balance between pathogens and other soil microbes. Finally, we will indicate potential future avenues to improve the resistance and/or recovery of natural biocontrol during and after water stresses. As such, our perspective paper will highlight a knowledge gap that needs to be bridged to adapt agricultural ecosystems to changing climate scenarios.